Specialization, Outsourcing and Wages - Jakob Roland Munch; Jan Rose Skaksen (Copenhagen Business School (CBS), Department of Economics, 2006)
This paper studies the impact of outsourcing on individual wages. In contrast to the standard approach in the literature, we focus on domestic outsourcing as well as foreign outsourcing. By using a simple theoretical model, we argue that, if outsourcing is associated with specialization gains arising from an increase in the extent of the market for intermediate goods, domestic outsourcing tends to increase wages for both unskilled and skilled labor. We use a panel data set of workers in Danish manufacturing industries to show that domestic and foreign outsurcing affect wages as predicted by the theory.
hdl:10398/7522
Keywords: C23; F16; J31; 330; Outsourcing; Comparative advantage; Specialization; Wages